The contribution of vegetation stratification and soil quality index in post-coal mining lands - Herman, Welly; Iskandar, Iskandar; Budi, Sri Wilarso; Pulunggono, Heru Bagus; Kurniati, Kurniati; Rahmayuni, Erlina (Journal of Degraded and Mining Lands Management, 2025)
Open-pit coal mining causes environmental degradation, disrupting ecosystem functions and reducing soil quality. This study evaluated the contribution of vegetation stratification and the Soil Quality Index (SQI) in supporting the recovery of post-coal mining land. The research was conducted on revegetated sites of varying ages (2006-2022) within the PT Allied Indo Coal Jaya mining area in Sawahlunto, West Sumatra. Vegetation structure was analyzed based on five vertical strata: trees, poles, saplings, seedlings, and understory. Concurrently, soil quality was assessed using the SQI, which incorporates physical, chemical, and biological soil parameters. They showed that revegetated sites older than 10 years exhibited more complex vegetation structures and significantly higher SQI values. Among the strata, understory frequency showed the strongest correlation with SQI (r = 0.907), followed by tree density (r = 0.530), reflecting the crucial role of these two layers in enhancing organic matter, microbial activity, and soil stability. Principal Component Analysis (PCA) identified soil pH, organic carbon, total nitrogen, microbial biomass, and soil permeability as the key indicators contributing to SQI formation. These findings confirm that the interaction between vegetation stratification and soil quality plays a central role in accelerating ecosystem recovery and supporting the long-term sustainability of post-mining land revegetation.